Proportional representation, political responsiveness and child mortality - Gathmann, Christina (Discussion paper series, 2019)
There has been a longstanding debate about the link between political representation and health. In this article, I provide novel evidence that electoral reforms that shifted from a majoritarian to a proportional system of voter representation generated substantive health benefits for the general population. Using the exemplary case of Switzerland, I first show that the spread of proportional representation between 1890 and 1950 increased political participation and gave the working class, represented by left-wing parties, greater weight in the political process. Consistent with theories of the electoral system, proportional representation increased public investments, esp. in basic education, with few effects on redistribution or total spending. Based on comprehensive archival mortality statistics since 1890, I then demonstrate that the observed shifts in representation and public finances were associated with substantial declines in child mortality by 15% and in mortality from infectious diseases, the major killer of the time, by 10-15%.